Respostas
respondido por:
2
m²-12m+36=0
a=1; b=-12; c=36
Δ=b³-4ac
Δ=(-12)²-4*1*36
Δ=144-144
Δ=0
m'=-b+√Δ/2a
m=12+√0/2*1
m'=12/2
m'=6
m''=-b-√Δ/2a
m''=12-√0/2*1
m''=12/2
m''=6
Solução: A raiz da equação é 6!
a=1; b=-12; c=36
Δ=b³-4ac
Δ=(-12)²-4*1*36
Δ=144-144
Δ=0
m'=-b+√Δ/2a
m=12+√0/2*1
m'=12/2
m'=6
m''=-b-√Δ/2a
m''=12-√0/2*1
m''=12/2
m''=6
Solução: A raiz da equação é 6!
Anônimo:
Obrigado
respondido por:
0
Olá, boa noite ☺
Resolução:
m² - 12m +36=0.
Coeficientes:
a=1 , b=-12 , c=36.
Valor de delta:
Δ=b²-4.a.c
Δ=(-12)²-4.1.36.
Δ=144 - 144.
Δ=0.
Valores de x:
S={6}
Bons estudos :)
Resolução:
m² - 12m +36=0.
Coeficientes:
a=1 , b=-12 , c=36.
Valor de delta:
Δ=b²-4.a.c
Δ=(-12)²-4.1.36.
Δ=144 - 144.
Δ=0.
Valores de x:
S={6}
Bons estudos :)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás